Improved Performance of Dye-Sensitized Solar Cells With TiO2 Nano-Particles by Using The Carrot as a Dye Solar Cell Application - Hardani Hardani; Lily Maysari Angraeni; Cari Cari; Agus Supriyanto (Lambung Mangkurat University Press, 2019)
The aims of the research to were know performance of Dye-Sensitized Solar Cell (DSSC) using the dye of carrots (Daucus carota) as a photosensitizer with a variation of dye deposition area with spin coating techniques. The structure of the samples as a sandwich consisting of the working electrode titanium dioxide (TiO2), dye, electrodes of platinum (Pt) and the electrolyte sandwiched between two electrodes. Test absorbance dye using UV-Visible Spectrophotometer Lambda 25, using a two-point conductivity test probes El Kahfi 100 and characterization test IV using a Keithley 2602A.. DSSC fabrication has been done using dye extract of carrots (Daucus carota) with a variety of solvent technique spin coating. The results show that dye extract of carrots (Daucus carota) have an absorbance spectrum of 380-520 nm range. From the results of the test using AM Simulator 1.5G (100 mW/ cm2) diesel simulator, it was found that the volume of TiO2 precursors affected the performance of DSSC solar cells and the overall conversion efficiency was 0.021% for the carrots (Daucus carota) dye with ethanol solvent and 0.037% for the carrots (Daucus carota) dye by solvent acetone.